Material and sedation-analgesia in the neonatal lumbar puncture procedure - Jimeno Ruiz, Sara; López Escobar, Alejandro; Riaza Gómez, Mónica; Cárdenas Rebollo, José Miguel (My University, 2024)
Introduction: Lumbar puncture (LP) is a frequent procedure during the neonatal period. Correctly performing this technique can avoid many of its complications. Objective: To evaluate the LP procedure in neonates in Spanish hospitals, studying the type of material and the sedation-analgesia used. Material and methods: Cross-sectional study conducted in Spain gathering data through a survey research distributed by email through the Segurneo-SEN Hospital Network and the Spanish Neonatal Society. Data on the LP technique in neonates were collected. Results: A total of 301 participants were analysed. Most professionals used a trocar needle with a stylet as the first option (89.7%); however, when the LP failed or was blood-stained, 32.2% changed the type of needle. A total of 143 doctors gave their subjective feeling about the type of needle: they only use trocar needles with stylet (41.3%), the technique is easier using scalpvein needles (32.2%), there is less probability of a blood-stained LP, or failed using scalp-vein needles (7.7%), they choose the type of needle depending on the size of the newborn (10.5%), indifference when using one type or another needle (8.4%). Almost all (99%) of the surveyed doctors used some type of analgesia. The most widely used measures were topical anaesthetics (90.3%) and sucrose (82.2%).